18.4: Full‐Color Active‐matrix Mini‐LED Display based on Novel Color Conversion Technology. (26th August 2021) - Yin, Yongming; Peng, Wenxiang; Geng, Jing; Bai, Xue; Duan, Miao; Wu, Yongwei; Hou, Jun; Li, Dongze; Hwang, Jason; Zhang, Xin; Meng, Hong
Abstract : Mini/Micro LED displays have attracted widely attention due to its excellent display performance. In this paper, a novel full‐color Mini‐LED display based on blue Mini‐LED chips and quantum dots (QDs) was demonstrated. Based on this structure, ultra‐high color gamut was achieved. We believe this strategy could make the best of both LEDs and QDs and would be further developed as an alternative route to obtain full‐color Mini‐LED displays.